Application of Commercial Software to the Classification of Suicide Cases: A Brief Report. - Rezaeian, Mohsen; Dunn, Graham; St Leger, Selwyn; Appleby, Louis (Violence & Victims, 2011)
Mosaic Profiler software was used to classify suicide and open verdict cases during 1996 to 1998 in England and within England, for the London and the North West regions. The classification system was based on the socioeconomic characteristics of the last place of residence of the cases at the level of postcode. The results highlighted that deprived areas and areas that contain elderly population or those areas that suffer from lack of social cohesion are overrepresented, whereas affluent areas are underrepresented. All of these, although in the larger scale, seem to support the results of other studies. Nevertheless, more studies would be required before one can fully evaluate the application of the Mosaic Profiler in the field of spatial epidemiology. [PUBLICATION ABSTRACT].